Novel thermal management system using mist cooling for lithium-ion battery packs - Saw, Lip Huat; Poon, Hiew Mun; Thiam, Hui San; Cai, Zuansi; Chong, Wen Tong; Pambudi, Nugroho Agung; King, Yeong Jin (Elsevier, 2018)
Thermal management system is crucial for a Lithium-ion battery pack as cycle life, driving range of electric vehicle, usable capacity and safety are heavily dependent on the operating temperature. Optimum operating temperature of Lithium-ion battery pack is about 25-40 °C. Power availability of the battery pack may differ according to the operating temperature. Although air cooling is the simplest and cheapest cooling solution, the cooling capacity is still limited by the low specific heat capacity. This will cause large variation of temperature of cells across the battery pack. In this study, mist cooling is proposed for battery pack thermal management system. Experiments and numerical simulations are conducted to investigate the thermal performance of conventional dry air cooling and mist cooling. Simulation results are then validated with the experimental data. The simulation results show that mist cooling can offer lower and more uniform temperature distribution compared to dry air cooling. Mist cooling with mass flow rate of 5 gs−1 and 3% mist loading fraction is sufficient to ensure the surface temperature of the battery module maintained to below 40 °C. Therefore, mist cooling is a potential solution for the thermal management system of Lithium-ion battery pack.